Evaluation of rail terminals in container ports using simulation: A case study. (December 2021) - Sadeghi, Moein; Bagheri, Morteza; Pishvaee, Mir Saman
The purpose of this research is to define the bottlenecks in a port's rail container transport process and simulate the proposed scenarios in a real port using the lean-railroading approach. After visiting the selected port and holding several meetings with the authorities, all functions relating to containers have been identified. Each section's arrival and departure times were used in this analysis for all containers shipped by rail in 2017, including 19, 000 records. The data was accomplished by the processing time of transferring the containers between the railway areas and the port berth. The value stream map (VSM) related to the processes was prepared using the lean approach, the current port situation and proposed scenarios were simulated using the AnyLogic software. The results showed that the two proposed solutions effectively reduced time and costs by up to 20%. The research port also could increase the rail share to 8% without spending on infrastructure. Nevertheless, the rail container terminal warehouse will be a significant bottleneck for the port by growing the load operations. Reducing the turnover of the wagon will also halve the required number of wagons in the network. Therefore, it is recommended that a framework be established to direct freight to rail transport through the Ports Organization by meeting the infrastructure and operational requirements of the port and through the Railroad Company by launching the scheduled freight train and providing the required fleets.